ELKS1 localizes the synaptic vesicle priming protein bMunc13-2 to a specific subset of active zones - Kawabe, Hiroshi; Mitkovski, Miso; Kaeser, Pascal S.; Hirrlinger, Johannes; Opazo, Felipe; Nestvogel, Dennis; Kalla, Stefan; Fejtova, Anna; Verrier, Sophie E.; Bungers, Simon R.; Cooper, Benjamin H.; Varoqueaux, Frederique; et al. (The Journal of Cell Biology, 2017)
Presynaptic active zones (AZs) are unique subcellular structures at neuronal synapses, which contain a network of specific proteins that control synaptic vesicle (SV) tethering, priming, and fusion. Munc13s are core AZ proteins with an essential function in SV priming. In hippocampal neurons, two different Munc13s-Munc13-1 and bMunc13-2-mediate opposite forms of presynaptic short-term plasticity and thus differentially affect neuronal network characteristics. We found that most presynapses of cortical and hippocampal neurons contain only Munc13-1, whereas ∼10% contain both Munc13-1 and bMunc13-2. Whereas the presynaptic recruitment and activation of Munc13-1 depends on Rab3-interacting proteins (RIMs), we demonstrate here that bMunc13-2 is recruited to synapses by the AZ protein ELKS1, but not ELKS2, and that this recruitment determines basal SV priming and short-term plasticity. Thus, synapse-specific interactions of different Munc13 isoforms with ELKS1 or RIMs are key determinants of the molecular and functional heterogeneity of presynaptic AZs.
EVALuna2:33410